Entry Points : The Vera List Center Field Guide on Art and Social Justice No. 1 - Haines, Chelsea; Kuoni, Carin (Vera List Center field guide on art and social justice, 2019)
Providing a lively snapshot of the state of art and social justice today on a global level, Entry Points accompanies the inaugural Vera List Center Prize for Art and Politics, launched at The New School on the occasion of the center's twentieth anniversary. This book captures some of the most significant worldwide examples of art and social justice and introduces an interested audience of artists, policy makers, scholars, and writers to new ways of thinking about how justice is defined, advanced, and practiced through the arts. In so doing, it assembles some of the latest scholarship in this field while refining our vocabulary for speaking about social justice, social engagement, community enhancement, empowerment, and even art itself. The book's first half contains three essays by Thomas Keenan, João Ribas, and Sharon Sliwinski that map the field of art and social justice. These essays are accompanied by more than twenty profiles of recent artist projects that consist of brief essays and artist pages. This curated and carefully considered map of artists and projects identifies key moments in art and social justice. The book's second half consists of an in-depth analysis of Theaster Gates's The Dorchester Projects, which won the inaugural Vera List Prize for Art and Politics. Produced to complement the project's exhibition at the Sheila C. Johnson Design Center, Parsons School of Design in September 2013, this analysis illuminates Gates's rich, complex, and exemplary work. This section includes an interview between Gates and Vera List Center director Carin Kuoni; essays by Horace D. Ballard Jr., Romi N. Crawford, Shannon Jackson, and Mabel O. Wilson; and a number of responses to The Dorchester Projects by faculty in departments across The New School.